Running repeatable and controlled virtual routing experiments. (8th October 2013) - Abeni, Luca; Kiraly, Csaba
Summary This paper describes an approach to perform reproducible performance tests on virtual routers, comparing different virtual routing architectures, different software versions and configurations. The presented approach is based on VRKit, a software tool that allows to build pre‐configured bootable virtual router images with the desired characteristics. Design decisions are described, and some usage examples are presented, showing how the tool can be used for research on virtual routing, facilitating performance comparison of various virtual router implementations. Copyright © 2013 John Wiley & Sons, Ltd.